Pengembangan Genre melalui Microsoft Powerpoint sebagai Media E-Learning dalam Memahami Teks Berbahasa Inggris pada Masa Covid-19 di SMA N 1 Bongas Indramayu - Ahmad Fauzan; Isna Amanaturrakhmah (LITERASI (Jurnal Ilmu Pendidikan), 2021)
Based on Circular Letter of Educational Authorities of West Java Province Number 443/5867-Set.Disdik regarding the extension of the teaching and learning process implementation time at home and the mandate of the Head of Educational Authorities (Disdik), Dewi Sartika, taking into account a number of matters related to Covid-19 (Pikiran Rakyat, 01 - 04 June 2020, 12:45 WIB), the implementation of education in West Java Province is carried out with the long distance learning mechanism. By paying attention to this policy, SMA N 1 Bongas Indramayu West Java carries out a distance learning process (online) through electronic media (E-Learning). Thus, teachers must be more creative and innovative in choosing and implementing appropriate learning methods so their students’ problems in the form of low reading skills and difficulties in understanding English reading texts can be resolved properly. This study aims to test and produce learning media in the form of genres through Microsoft PowerPoint and to improve students' reading comprehension skills in understanding English texts. Therefore, this learning media is very helpful for English teachers in improving students' reading comprehension skills in understanding English texts through long distance learning during the Covid-19 period. Referring to Sugiyono (2013: 407-427), this research is categorized as research and development (R&D). The study population was all students of SMA N 1, Bongas District, Indramayu Regency, totaling 522 students, 216 boys and 306 girls. This research applied Random sampling technique. The sample was 29 students of Class XII MIPA-3 (15 boys and 14 girls) with the assumption that they already had basic reading comprehension skills in English in the previous class; and as material stabilization before they carry out the national/school final exams.. Before giving treatment by applying the genre through Microsoft PowerPoint as a learning medium, students were given a pre-test. This is done to see the basic abilities of students before treatment. After the learning (treatment), students did the post-test.This was done to know the improvement of students' understanding ability in reading English texts. The instrument used in this study was an objective test in the form of multiple choices of which validity was tested through expert judgment (Sugiyono, 2013: 177) and point-biserial correlation test (Azwar, 2011: 19-21) and its reliability was tested using the Kuder-Richardson test (KR-20), Azwar (2011: 82). The data from the pre-test and post-test results were analyzed through the related t-test and were described (Sugiyono, 2013: 422). The results showed that the learning method by applying the genre through Microsoft PowerPoint was very effective in improving students' comprehension skills in reading English-language texts through distance learning (online) during the Covid-19 period. This can be seen from the value of t-test = -17,792 with a value of t-table = 2.052 with degree of freedom (df) n-2 = 27 at an error level of 5% in the area of acceptance Ha and rejection of H0. This explains the significant difference between the learning method by media of genre through Microsoft PowerPoint and the previous method.Keywords: development, media, genre, reading, understanding